Classifying ambiguous melanocytic lesions with FISH and correlation with clinical long-term follow up - Gaiser, Timo; Kutzner, Heinz; Palmedo, Gabriele; Siegelin, Markus David; Wiesner, Thomas; Bruckner, Thomas; Hartschuh, Wolfgang; Enk, Alexander; Gaiser, Maria (Modern pathology, 2010)
Recently, initial studies describing the use of multicolor fluorescence in situ hybridization (FISH) for classifying melanocytic skin lesions have been published demonstrating a high sensitivity and specificity in discriminating melanomas from nevi. However, the majority of these studies included neither histologically ambiguous lesions nor a clinical long-term follow up. This study was undertaken to validate a special multicolor FISH test in histologically ambiguous melanocytic skin lesions with known clinical long-term follow up. FISH was scored by three independent pathologists in a series of 22 melanocytic skin lesions, including 12 ambiguous cases using four probes targeting chromosome 6p25, centromere 6, 6q23, and 11q13. The FISH results were compared with array comparative genomic hybridization data and correlated to the clinical long-term follow up (mean: 65 months). Pair-wise comparison between the interpretations of the observers showed a moderate to substantial agreement (κ 0.47-0.61). Comparing the FISH results with the clinical behavior reached an overall sensitivity of 60% and a specificity of 50% (χ2=0.25; P=0.61) for later development of metastases. Comparison of array comparative genomic hybridization data with FISH analyses did not yield significant results but array comparative genomic hybridization data demonstrated that melanocytic skin lesions with the development of metastases showed significantly more chromosomal aberrations (P<0.01) compared with melanocytic skin lesions without the development of metastases. The FISH technique with its present composition of locus-specific probes for RREB1/MYB and CCND1 did not achieve a clinically useful sensitivity and specificity. However, a reassessment of the probes and better standardization of the method may lead to a valuable diagnostic tool.
Gesehen am 24.10.2023